Establishment of Larix kaempferi MSAP System Based on Capillary Electrophoresis / 基于毛细管电泳的日本落叶松MSAP反应体系的建立 - 刁姝; 孙超; 孙晓梅; 张守攻 (Forest research (Beijing), 2017)
[Objective] This study aims at constructing the excellent reaction system of MSAP technology and obtaining DNA methylation maps with clear bands and uniform signal intensity, so as to provide references for the study on genetic variation of Larix kaempferi in the future.[Method] Taking immature xylem as experimental materials, the impact of five factors (dosage of DNA template, concentration of primers, Mg2+, dNTP and exTaq DNA polymerase) on the result of capillary electrophoresis was investigated. [Result] It was found that different concentrations of DNA template and the exTaq DNA polymerase did not affect the result of capillary electrophoresis. However, high concentration of primers would lead to sparse fragments in MSAP profile. Mg2+ concentration and dNTP concentration were the most important factors which determined the result of capillary electrophoresis. When the concentration of Mg2+/dNTP was unsuitable, the amount of band would significantly decrease, and the amount of impurity peak would signific